Promoting participation in health in the community using a health survey - Roberts, Heather (1993)
Health promotion is an emerging discipline that seeks to enhance positive health and prevent ill health. This thesis is designed to inform practice in health promotion. It is based on an action research project that draws together interdisciplinary concepts of the measurement of health and community participation. In so doing it identifies the use of a survey, the Community Health Promotion Survey (CHPS). The thesis argues that when used creatively in this way a survey may simultaneously serve two purposes: first, measure health-related behaviour and, secondly, promote participation in health within a community. Thus, in this study, the survey process and its impact on the lay community were considered to be as important as the measurements of health-related behaviour obtained.